Wounded falcons - Buitrago, Jairo (Groundwood Books/House of Anansi Press, 2021)
"A story about the heart-opening effect that taking care of a wounded creature has on a wounded boy, from acclaimed picture-book creators Jairo Buitrago and Rafael Yockteng. Adrián is always in trouble, at school and at home, while Santiago gets along quite well. But they are friends. When Adrián finds a wounded bird in an abandoned lot in the midst of the city, things begin to change. Taking care of the bird, learning all about it, discovering that it is a falcon, loving it -- and accepting what this love means -- gives Adrián a chance to show others a glimpse of who he truly is. Santiago has always known that Adrián has a big heart, and his steadfast friendship is also the reason Adrián has a chance to heal."--
Aus dem Spanischen übersetzt
Keywords: Falcons / Juvenile fiction; Friendship / Juvenile fiction; Human-animal relationships / Juvenile fiction; Animal rescue / Juvenile fiction; Birds / Juvenile fiction; Helping behavior / Juvenile fiction; Friendship / Fiction; Animals / Fiction; Birds / Fiction; Faucons / Romans, nouvelles, etc. pour la jeunesse; Amitié / Romans, nouvelles, etc. pour la jeunesse; Relations homme-animal / Romans, nouvelles, etc. pour la jeunesse; Animaux / Sauvetage / Romans, nouvelles, etc. pour la jeunesse; Oiseaux / Romans, nouvelles, etc. pour la jeunesse; Comportement d'aide / Romans, nouvelles, etc. pour la jeunesse; JUVENILE FICTION / Animals / Birds; JUVENILE FICTION / Social Themes / Friendship; Animals; Birds; Friendship; Falcons / Fiction; Wildlife conservation / Fiction; Conduct of life / Fiction; Latin Americans / Fiction; Außenseiter; Falken; Selbstvertrauen; Pflege; Verwundung; Bilderbuch